Merdeka Belajar Episode 7: Sekolah Penggerak - Zulkarnaen Zulkarnaen; Mukhlis Mukhlis; Jamaludin Abdullah (Journal on Education, 2024)
The Driving School Program is an initiative that aims to improve the quality of education in Indonesia. This program emphasizes the holistic development of student learning outcomes with a primary focus on achieving the Pancasila Student Profile. This profile includes the improvement of cognitive competencies, such as literacy and numeracy, as well as noncognitive competencies that include character development. The essence of this program is to start efforts to improve education with superior human resources, which include principals and teachers. The principals and teachers involved in the Mobilizing School are not only committed to improving student learning outcomes in their own schools, but they also act as influencers who share knowledge, best practices, and experiences with other education units in different regions. Through the Sekolah Pengmobilizer program, it is expected that education in Indonesia will experience significant improvements, with increased student competence in literacy and numeracy, as well as strong character development. By focusing on developing superior human resources and cooperation between schools, this program is an important foundation in efforts to achieve a better quality of education throughout Indonesia.